Predictive Feedback and Conscious Visual Experience - Panichello, Matthew F.; Cheung, Olivia S.; Bar, Moshe (Frontiers in Psychology, 2013)
The human brain continuously generates predictions about the environment based on learned regularities in the world. These predictions actively and efficiently facilitate the interpretation of incoming sensory information. We review evidence that, as a result of this facilitation, predictions directly influence conscious experience. Specifically, we propose that predictions enable rapid generation of conscious percepts and bias the contents of awareness in situations of uncertainty. The possible neural mechanisms underlying this facilitation are discussed.